Sports and Functional Training Improve a Subset of Obesity-Related Health Parameters in Adolescents: A Randomized Controlled Trial - Branco, Braulio Henrique Magnani; Mariano, Isabela Ramos; de Oliveira, Leonardo Pestillo; Bertolini, Sônia Maria Marques Gomes; de Oliveira, Fabiano Mendes; Araújo, Cynthia Gobbi Alves; Adamo, Kristi (Frontiers in Psychology, 2021)
To investigate the effects of two different modes of physical activity on body composition, physical fitness, cardiometabolic risk, and psychological responses in female adolescents participating in a multi-disciplinary program. The 12-week randomized intervention included 25-adolescents with overweight divided into two groups: sports practice-SPG and functional training-FTG. The SPG intervention was divided into three sports: basketball, handball, and futsal. SPG participants performed one sport 3-times/week, over the course of one month. The FTG performed concurrent exercises 3-times/week. This study was registered in the Clinical Trials Registry Platform. The intensity of physical exercises-PE was matched between groups by the rating of perceived exertion. The primary outcome was body composition, and secondary outcomes were physical fitness, cardiometabolic risk, and psychological responses. There was a significant time-effect for body mass, BMI, and LDL-c, all being reduced. There were increases over time for musculoskeletal mass, aerobic fitness, and HDL-c (p<0.05). There was a group x time interaction with body fat percentage being lower post-intervention in the SPG (p<0.05). No significant differences were observed for the other variables. Both PE models were effective in improving a subset of obesity-related health parameters. The findings should be extended by further investigation using more sophisticated measures of energy expenditure.